2019
DOI: 10.1186/s41018-019-0053-z
|View full text |Cite
|
Sign up to set email alerts
|

Getting relief to marginalised minorities: the response to cyclone Komen in 2015 in Myanmar

Abstract: Little academic research has examined the challenges humanitarian actors face or the strategies they develop in the increasingly numerous authoritarian and low-intensity conflict settings. Based on 4 months of qualitative fieldwork in Myanmar in 2017-2018, this article explores how civil society organisations, international nongovernmental organisations, international organisations, and donor agencies tried to provide relief to marginalised minorities in the ethnic States of Chin and Rakhine following Cyclone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…We found that most households had to rely on their own agency, assets and aid from non-governmental organisations, rather than state-authorities' support, to cope with Komen's impacts. This fits with perceptions of a 'marginalising government response ' and '[u]nion government […] neglect' towards the disaster-affected Chin population in Komen's aftermath (Desportes 2019).…”
Section: Addressing Climate-related Livelihood Riskssupporting
confidence: 69%
“…We found that most households had to rely on their own agency, assets and aid from non-governmental organisations, rather than state-authorities' support, to cope with Komen's impacts. This fits with perceptions of a 'marginalising government response ' and '[u]nion government […] neglect' towards the disaster-affected Chin population in Komen's aftermath (Desportes 2019).…”
Section: Addressing Climate-related Livelihood Riskssupporting
confidence: 69%
“…In such settings, NGOs often exclude highly stigmatized groups from their programming, expecting fundraising to be impossible. For instance, flood operations in Malaysia have excluded the Rohingya minority (Desportes 2019), relief operations in Yemen have excluded the Al-Akhdam people of African descent (Housing and Land Rights Network 2006), and NGOs in Pakistan have excluded transgender individuals from their aid programs (Rumbach and Knight 2014). We found that even when appeals emphasized the Roma ethnicity of beneficiaries, some donations were still made both in the experiment and in our qualitative data.…”
Section: Discussionmentioning
confidence: 71%
“…The data were thematically analyzed in two phases, following Braun and Clarke (2006). First, contextspecificities, historical pathways, and nuances were drawn out for each case (see Desportes, 2019;Desportes, 2020;Desportes et al, 2019). Second, contrasts and similarities were sought across cases (e.g., by revisit- Notes: Participant numbers refer to individual in-depth interviews, except for the counts of community members, who sometimes participated in focus groups.…”
Section: Methodsmentioning
confidence: 99%
“…Literature on LIC and authoritarian dynamics directs our attention to the structural and cultural means through which power and violence are expressed (Galtung, 1996). Everyday politics are central in that legal instruments, bureaucracy, and daily engagements with government officials or community leaders restrict or influence aid access, activities, and beneficiary selection (Desportes, 2019;Hilhorst, 2013). Authoritarian modes of control involve establishing restrictions but also instilling a culture of uncertainty and fear (Glasius et al, 2018).…”
Section: Disaster Politics In Authoritarian Low-intensity Conflict Settingsmentioning
confidence: 99%
See 1 more Smart Citation